Storage of Gas in Aquifers in Porous Media and Creation of Under-ground Gas Storage (UGS) - Aliyeva, O.A.; Аliyev А.S. (Herald of Azerbaijan Engineering Academy, 2025)
The article shows planned solutions for creating underground gas reservoirs in a porous me-dium. Formulas for the volumes of produced and injected gas were obtained for each solution. As pressure values change, the volume of stored gas will also change. In this case, the pressure in the underground gas reservoir will vary from maximum to minimum depending on the operating con-ditions of surface equipment and the minimum permissible flow rate of the gas well. There are two types of underground gas storage in porous media: one is exhausted gas, and the other is gas storage in oil fields and aquifers. The article defines the difference between residual, active, buffer and maximum gas volumes in the design and operation of underground gas reservoirs. During the cre-ation and operation of reservoirs underground gas is also determined by the difference between the maximum, minimum and average permissible pressure. At the same time, technological calculation of the gas tank consists of finding connections between the main indicators that correspond to the optimal, that is, the minimum reduced costs. All layers created in aquifers, as well as layers created on the basis of depleted oil and gas fields, characterized by water-pressure and elastic-pressure regimes, were also calculated taking into account the movement of formation waters.